2017
DOI: 10.1039/c7sc03189k
|View full text |Cite
|
Sign up to set email alerts
|

Programmed serial stereochemical relay and its application in the synthesis of morphinans

Abstract: A rationally designed, serial point-to-axial and axial-to-point stereoinduction and its integration into a multi-step and target-oriented organic synthesis was demonstrated in a novel chemical method to access morphinans and it is potentially applicable to other structurally related alkaloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 88 publications
1
5
0
Order By: Relevance
“…10 Similar SET conditions have been recently reported by Akai to promote biaryl racemization at 35–50 °C, which underpins the development of an enzymatic dynamic kinetic resolution of biaryls in the same laboratory 11. Chen has also found that oxidation with a hypervalent iodine reagent promotes BINOL racemization 12. The precise mechanistic origins to explain why biaryl oxidation should render more facile axial rotation, leading to easier racemization, remain unclear.…”
Section: Introductionsupporting
confidence: 57%
“…10 Similar SET conditions have been recently reported by Akai to promote biaryl racemization at 35–50 °C, which underpins the development of an enzymatic dynamic kinetic resolution of biaryls in the same laboratory 11. Chen has also found that oxidation with a hypervalent iodine reagent promotes BINOL racemization 12. The precise mechanistic origins to explain why biaryl oxidation should render more facile axial rotation, leading to easier racemization, remain unclear.…”
Section: Introductionsupporting
confidence: 57%
“…Hypervalent iodine compounds have been found to facilitate the rotation of biaryl bonds. 22 In our experiments, phenyliodine(III) diacetate (PIDA, 5 mol %) catalyzed the racemization of (R)-1 in an HFIP/CH 2 Cl 2 solution [1:1 ratios (Figure 1B, pink circles)]. The electron paramagnetic resonance (EPR) spectrum of this solution (Figure 1C) reveals radical species that correspond to the simulated spectrum of the binaphthoxyl radical (1•).…”
mentioning
confidence: 68%
“…Chen and co-workers' alternative synthetic approach to the morphinan family of natural products was developed from their method of oxidative dearomatization of atropisomerically pure biaryl phenols to achieve complex intramolecular Diels− Alder products such as 303. 100 To demonstrate the synthetic utility of these intermediates, 303 was elaborated into lactam 305 via Beckmann rearrangement of oxime 304 (Scheme 42). Reduction of the amide, followed by Hoffmann elimination, induced further cleavage of the bridgehead C−N bond to furnish amine 306.…”
Section: Total Syntheses Of Morphinanmentioning
confidence: 99%